A multifaceted approach in promoting positive mental health culture in Hong Kong secondary schools: The Mindshift educational networking programme. Issue 10 (28th November 2021) - Suen, Yi Nam; Lam, Oi Bun Christina; Chan, Kai Tai; Wong, Tak Hing Michael; Lui, Sai Yu Simon; Chan, Yuk Yu Vinci; Lam, Hoi Ying; Wong, Ming Yin Stephanie; Hui, Lai Ming Christy; Lee, Ho Ming Edwin; Chang, Wing Chung; Chan, Kit Wa Sherry; et al.
Abstract: Aim: Many young people with mental health problems refuse to seek help because of stigma and leave the problem untreated. Previous research suggests that contact interventions with education could improve the stigma of mental illness in young people, thereby encouraging help‐seeking in distress. The current study examined the effectiveness of a multifaceted programme, the Mindshift educational networking programme (MENP), in promoting a positive mental health culture in Hong Kong secondary schools. Methods: The MENP provided activities at school, teacher and student levels to 14 Hong Kong secondary schools. School activities included visits, mental health talks and support for capstone projects. While teachers participated in workshops and regional seminars, students received ambassador training workshops, contact opportunities with people with psychosis and attachment programmes. The impact of MENP was evaluated by changes in students' knowledge, attitudes and behaviours toward people with psychosis and mental illness before and after the programme, as well as by teachers' feedback on the programme. Results: This study analysed data from 55 students and 20 teachers. It was found that the MENP improved students' knowledge of mood symptoms ( p = .03), acceptance of people with psychosis ( p = .04) and intended behaviour toward people with mental illness ( p = .02). The feedback of the teachers on the programme was positive. Conclusions: The results support the application of the multifaceted approach to promote a positive mental health culture in schools. The findings call on the government to implement the programme in schools in Hong Kong by providing financial support to relevant organizations.